Implementation of a National Identity Number-Based Identity Card Policy In Pasangkayu Regency - Sadek, Irfan Rusli; Latief, Juraid Abdul; Natsir, Nawawi; Daswati, Daswati (Journal of Asian Multicultural Research for Economy and Management Study, 2021)
The policy development mechanism for the national identity number -based electronic ID card software is described in this report. In this analysis, a qualitative procedure was used in conjunction with a case study technique. The total number of informants was 19. Employees from the government who work on the national identity number -based electronic identification card software make up this group. The culture is often used as a source of information in this report. The findings of the study indicate that; Every organ and implementor personnel at every level in every Pasangkayu sub-district office understands and implements national Identity Number -based electronic identification card policy requirements and goals, namely: first, citizens with a identification card condition have the right to get a electronic identification card, which the government is required to promote. Second, get closer to the position where the community resides, in this case the office respective districts, such that the community is not inconvenienced and burdened, must go to the Disdukcapil office in the district capital. Third, since these programs are provided free of charge or at no expense to government, this approach would not impose an economic burden. Fourth, this proposal has little effect on the district’s spending schedule. As a result, success policy is essentially an evaluation of how well expectations and policy priorities have been met. As a result, the policy’s standards and objectives must be practical and specifically targeted, and any implementation entity (implementor) must be aware of the policy’s standards and objectives.